A review of 250 years of South African bee taxonomy and exploration (Hymenoptera: Apoidea: Anthophila). Issue 1 (2nd January 2019) - Melin, A.; Colville, J.F.
Abstract : South Africa is recognised as a global centre of bee diversity. Here we assess the status of taxonomic activity and exploration of its bee fauna over the past 250 years. The rate of species description for bees has been increasing at a constant level since the 1950s. However, our data shows an increase in the species described per taxonomist, suggesting a number of bee species still remain undiscovered. Reinforcing this conclusion, over two thirds of South Africa has been critically under-sampled for bees and ∼98% of the country has received little survey effort (<100 records per ∼ 25 km × 25 km grid cell). Decline in local taxonomic capacity and an increase in ecosystem service, pollination and conservation research highlights the immediate need for developing expertise in South African bees. DNA barcoding is therefore seen as an important component of future integrative taxonomic approaches. At present, <10% of South African bee species have sequences available, with only ∼3% for specimens collected within South Africa. We suggest that the results presented here may be reflective of the general knowledge of South Africa's entomofauna. To expedite the documentation and exploration of insects – an economic and ecologically important group facing increased threats of extinction – demands urgent commitment and investment from universities, research institutions and government.